Small‐scale purification of butyrylcholinesterase from human plasma and implementation of a μLC‐UV/ESI MS/MS method to detect its organophosphorus adducts. Issue 10 (31st March 2015) - John, Harald; Breyer, Felicitas; Schmidt, Christian; Mizaikoff, Boris; Worek, Franz; Thiermann, Horst
<x xml:space="preserve">Abstract</x> Human butyrylcholinesterase (hBChE) is a serine hydrolase (EC 3.1.1.8) present in all mammalian tissues and the bloodstream. Similar to acetylcholinesterase, the enzyme reacts with organophosphorus compounds (OP) like nerve agents or pesticides that cause enzyme inhibition (BChE adducts). These adducts represent valuable biomarkers for analytical verification of OP exposure. For establishment of these mass spectrometry based methods sufficient amounts of hBChE in high purity are required. Unfortunately, commercial lots are of inappropriate purity thus favouring in‐house isolation. Therefore, we developed a small scale procedure to isolate hBChE from citrate plasma. After precipitation by polyethylene glycol (8% w/v and 20% w/v PEG 6000) hBChE was purified from plasma by four consecutive chromatographic steps including anion exchange, affinity extraction and size exclusion. Protein elution was monitored on‐line by UV‐absorbance (280 nm) followed by continuous fractionation for off‐line analysis of (1) hBChE enzyme activity by Ellman assay, (2) protein purity by gel electrophoresis, and (3) protein identity by matrix‐assisted laser desorption/ionization mass spectrometry (MALDI MS). Numerous major impurities separated from hBChE were identified. The purified material was used for in vitro incubation with diverse OP to establish a μ‐liquid chromatography‐ultra violet detection/electrospray ionization tandem‐mass spectrometric method (μLC‐UV/ESI MS/MS) for detection of hBChE adducts suitable for verification analysis. Analytical data for diverse OP pesticides including deuterated analogues as well as G‐ and V‐type nerve agents and their precursor are summarized. This method was successfully applied to plasma samples provided by the Organisation for the Prohibition of Chemical Weapons (OPCW) for the 4th Biomedical Exercise. Copyright © 2015 John Wiley & Sons, Ltd.